Beaten but not down! Exploring resilience among female sex workers (FSWs) in Nairobi, Kenya - Rhoda Wanjiru; Emily Nyariki; Hellen Babu; Ibrahim Lwingi; Jennifer Liku; Zaina Jama; Mary Kung’u; Polly Ngurukiri; The Maisha Fiti Study Champions; Chrispo Nyamweya; Pooja Shah; Monica Okumu; et al. (BMC Public Health, 2022)
Abstract Background In Kenya sex work is illegal and those engaged in the trade are stigmatized and marginalized. We explored how female sex workers in Nairobi, Kenya, utilize different resources to navigate the negative consequences of the work they do. Methods Qualitative data were collected in October 2019 from 40 FSWs who were randomly sampled from 1003 women enrolled in the Maisha Fiti study, a 3-year longitudinal mixed-methods study exploring the relationship between HIV risk and violence and mental health. All interviews were audio-recorded, transcribed and translated. Data were thematically coded and analyzed using Nvivo 12. Results Participants’ age range was 18–45 years. Before entry into sex work, all but one had at least one child. Providing for the children was expressed as the main reason the women joined sex work. All the women grew up in adverse circumstances such as poor financial backgrounds and some reported sexual and physical abuse as children. They also continued to experience adversity in their adulthood including intimate partner violence as well as violence at the workplace. All the participants were noted to have utilised the resources they have to build resilience and cope with these adversities while remaining hopeful for the future. Motherhood was mentioned by most as the reason they have remained resilient. Coming together in groups and engaging with HIV prevention and treatment services were noted as important factors too in building resilience. Conclusion Despite the adverse experiences throughout the lives of FSWs, resilience was a key theme that emerged from this study. A holistic approach is needed in addressing the health needs of female sex workers. Encouraging FSWs to come together and advocating together for their needs is a key resource from which resilience and forbearance can grow. Upstream prevention through strengthening of education systems and supporting girls to stay in school and complete their secondary and/or tertiary education would help them gain training and skills, providing them with options for income generation during their adult lives.